قدرة التلاميذ على قراءة النصوص من كتاب حاشية الباجوري في معهد عز الرسالة سيباغا باغا بمندايلينج ناتل - Abdul Lohir Rosyid Nasution; Syaipuddin Ritonga; Zulpina (PT. Willy Print Art, 2025)
This study aims to determine the process of teaching reading, students' abilities, identify problems and find solutions in teaching reading with the book